Congenital Parotid Fistula: Surgical Management in Two Infants and Review of Literature - Swapnil Pattanshetti; Prema Menon; Shailesh Solanki; Akshay Saxena (Wolters Kluwer Medknow Publications, 2021)
Congenital salivary gland fistulas are uncommon. They develop as a result of abnormalities of the first and second branchial arches. Operative and nonoperative methods of management have been described. We report two rare cases of congenital parotid fistula presenting to us in infancy that were managed surgically.